DAMPAK STROKE DENGAN DEPRESI PADA PASIEN PASCA STROKE - T. Eltrikanawati; Resi Novia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Stroke is still a major chronic disease which is a world problem which is the cause of functional disorders due to the impact of stroke. The impact of a stroke is the result or consequences of a stroke in the form of the body's inability to perform certain activities or activities as usual and cause conditions of physiological, psychological, and structural abnormalities or anatomical function. Stroke survivors are at risk for depression. This study aims to determine the relationship between the impact of stroke and depression in post-stroke patients in the working area of the Sekupang Health Center. This type of research was an analytic study with a cross-sectional design, the sample in this study were 53 post-stroke patients. The sample used in this study was purposive sampling, the data analysis used was Kruskall Wallis, using a depression questionnaire, namely the Beck Depression Inventory Test and an observation sheet on the impact of stroke, namely the Barthel Index, obtained p value = 0.002 (0.05). This shows that there is a significant relationship between the impact of stroke and post-stroke depression in the work area of the Sekupang Batam Health Center. The conclusion is that stroke sufferers are advised to maintain a good lifestyle, be routinely re-controlled at the puskesmas, exercise diligently such as morning walks, maintain diet and regularity of taking medication, for health services it is necessary to procure banner advertisements and schedule health education for patients visiting the health services by describing stroke and its impacts, so that the health information can be read and the public understands the disease better.Keywords: Impact of stroke, Depression, Stroke